Designing controller for single area power plant using model order reduction method - Chandra, Gauri; Mathew, Lini; Negi, Richa (International Journal of Engineering and Technology, 2018)
A two-step method for designing controller for a single area power plant (SAPP) is proposed. In the first step, a lower-order (lth-order) model for a higher-order (hth-order) power plant is obtained using dominant pole retention and PadÃ© approximation method and a controller is designed for this model. This controller is then implemented to original higher-order power system in the next step. The method preserves stability and disturbance rejection is also satisfactory.Â